The cost-effectiveness of PCSK9 inhibitors - The Australian healthcare perspective. (15th September 2018) - Kumar, Radya; Tonkin, Andrew; Liew, Danny; Zomer, Ella
Abstract: Background: For patients in whom statins are not tolerated or effective as monotherapy, proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) represent a new class of lipid lowering therapies that may reduce low-density lipoprotein cholesterol (LDL-C) levels by up to 50% and lower cardiovascular events. While an important treatment option, the cost-effectiveness of PCSK9i in Australia remains unknown. This study aimed to determine the cost-effectiveness of PCSK9i compared to placebo in the prevention of atherosclerotic cardiovascular disease (CVD). Methods and results: A Markov cohort state-transition model was developed in Microsoft Excel. A hypothetical sample of 1000 individuals based on subjects in the Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk (FOURIER) trial populated the model. With each five-year cycle, model subjects could have non-fatal CVD events (myocardial infarction and/or stroke), or die from CVD or other causes. Follow-up was simulated for 25 years. CVD risk reduction, cost and utility data were gathered from published sources. At current acquisition prices (AU$8174 per person per year), the incremental cost effectiveness ratio (ICER) was AU$308, 558 per quality-adjusted life year (QALY) saved. Acquisition prices would need to be reduced to approximately AU$1500 per person per annum for PCSK9i to reach the arbitrary cost-effectiveness threshold of AU$50, 000 per QALY saved. Conclusion(s): PCSK9i are an effective alternative for those with existing CVD or at high risk of CVD in whom statin therapy alone is ineffective, but are not cost-effective to the Australian healthcare system based on current prices. Highlights: PCSK9 inhibitors are an efficacious alternative for those with statin intolerance. This is the first cost-effectiveness analysis of PCSK9 inhibitors in Australia. The analysis was from the Australian healthcare perspective. The model comprised a secondary prevention population based on the FOURIER study. At current prices, PCSK9 inhibitors would not be considered cost-effective.